Muskox status, recent variation, and uncertain future - Christine Cuyler; Janice Rowell; Jan Adamczewski; Morgan Anderson; John Blake; Tord Bretten; Vincent Brodeur; Mitch Campbell; Sylvia L. Checkley; H. Dean Cluff; Steeve D. Côté; Tracy Davison; et al. (Ambio, 2020)

Invasion, establishment, and range expansion of two parasitic nematodes in the Canadian Arctic - Susan J. Kutz; Sylvia Checkley; Guilherme G. Verocai; Mathieu Dumond; Eric P. Hoberg; Rod Peacock; Jessica P. Wu; Karin Orsel; Karin Seegers; Amy L. Warren; Arthur Abrams (Global Change Biology, 2013)
Climate warming is occurring at an unprecedented rate in the Arctic and is having profound effects on host‐parasite interactions, including range expansion. Recently, two species of protostrongylid nematodes have emerged for the first time in muskoxen and caribou on Victoria Island in the western Canadian Arctic Archipelago. Umingmakstrongylus pallikuukensis, the muskox lungworm, was detected for the first time in 2008 in muskoxen at a community hunt on the southwest corner of the island and by 2012, it was found several hundred kilometers east in commercially harvested muskoxen near the town of Ikaluktutiak. In 2010, Varestrongylus sp., a recently discovered lungworm of caribou and muskoxen was found in muskoxen near Ikaluktutiak and has been found annually in this area since then. Whereas invasion of the island by U. pallikuukensis appears to have been mediated by stochastic movement of muskoxen from the mainland to the southwest corner of the island, Varestrongylus has likely been introduced at several times and locations by the seasonal migration of caribou between the island and the mainland. A newly permissive climate, now suitable for completion of the parasite life cycles in a single summer, likely facilitated the initial establishment and now drives range expansion for both parasites.

Northwest passages: conservation genetics of Arctic Island wolves - Lindsey E. Carmichael; Julia Krizan; John A. Nagy; Mathieu Dumond; Deborah Johnson; Alasdair Veitch; Curtis Strobeck (Conservation Genetics, 2008)